Culture, empire, and the postcolony - David Murphy (Francosphères)
This article traces the relationship between culture, empire and the ‘postcolony’, focusing on the relationship between France and its former sub-Saharan African colonies. The first section examines the ongoing legacy of empire in France itself, which has been the subject of heated academic and political debates. The second part focuses on the 1966 Festival mondial des arts nègres (FESMAN) in Dakar and its recent revival in 2010, treating both events as case studies that allow us to explore the highly complex ways in which post-independence Senegalese/African culture has at different moments defined itself in relation/in opposition to French culture. The overall aim of the article is to reflect on the complex legacies of several centuries of French overseas expansion, as well as to consider the ways in which academics might develop new frameworks within which to assess what is problematically termed the French and Francophone worlds.